The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0008-6363(97)00262-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the vasorelaxant potency of nicorandil by metabolic inhibition and adenosine in the pig coronary artery

Abstract: Nicorandil produced a dose-dependent relaxation with a mean pEC50 (-log EC50, M) of 4.76 +/- 0.02. Inhibition of metabolism with carbonyl cyanide m-chlorophenyl hydrazone (CCCP, 100 nM) or by removal of extracellular glucose significantly increased the potency of nicorandil (pEC50s of 5.11 +/- 0.08 and 5.08 +/- 0.06, p < 0.05 in each case). The adenosine analogue 2-chloroadenosine (2-CA, 300 nM) had a similar effect (pEC50 = 5.17 +/- 0.06, p < 0.05). Reducing extracellular pH to 6.8 also significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Evidence that this is the case for levcromakalim has been obtained by Randall & Gri th (1993) and Randall et al (1994), who showed that hypoxia, inhibition of oxidative phosphorylation, or adenosine increased the potency of the drug in causing vasorelaxation in the rabbit ear artery, though the potency of pinacidil was una ected. In porcine coronary arteries, we have recently shown that nicorandil relaxations were enhanced by metabolic inhibition, decreased pH, or adenosine receptor activation, so in this respect the K + channel opening action of nicorandil appears to resemble that of levcromakalim rather than pinacidil (Davie & Standen, 1998). Our present results suggest that this is also so in rat small mesenteric arteries, since both inhibition of oxidative phosphorylation with CCCP and removal of glucose potentiated nicorandil-induced relaxations.…”
Section: The E Ect Of Metabolic Inhibition On Vasorelaxation By Nicorsupporting
confidence: 67%
“…Evidence that this is the case for levcromakalim has been obtained by Randall & Gri th (1993) and Randall et al (1994), who showed that hypoxia, inhibition of oxidative phosphorylation, or adenosine increased the potency of the drug in causing vasorelaxation in the rabbit ear artery, though the potency of pinacidil was una ected. In porcine coronary arteries, we have recently shown that nicorandil relaxations were enhanced by metabolic inhibition, decreased pH, or adenosine receptor activation, so in this respect the K + channel opening action of nicorandil appears to resemble that of levcromakalim rather than pinacidil (Davie & Standen, 1998). Our present results suggest that this is also so in rat small mesenteric arteries, since both inhibition of oxidative phosphorylation with CCCP and removal of glucose potentiated nicorandil-induced relaxations.…”
Section: The E Ect Of Metabolic Inhibition On Vasorelaxation By Nicorsupporting
confidence: 67%
“…The exact mechanisms of these effects have not been clearly identified. A recent study, however, indicated that metabolic inhibition significantly increased the potency of nicorandil on pig coronary artery relaxation (20). These results suggest that MgADP may enhance nicorandil induced KATP channel activities.…”
Section: Discussionmentioning
confidence: 88%
“…Its effectiveness as an anti-anginal may be increased by a synergistic action with the intrinsic metabolic sensitivity of the K ATP channel, so that it preferentially activates channels in ischaemic tissue. In vitro studies on coronary arteries suggest that it may have such a self-targeting action [171]. A further incentive to consider K ATP channel openers as anti-anginal drugs may be an added benefit of a cardiprotective effect that is probably mediated by cardiac rather than vascular channels [169,170].…”
Section: Vascular Effects Of Potassium Channel Openersmentioning
confidence: 99%